An importance of clinical proteomics for personalized medicine of lung cancer subtypes. Issue 2 (2016) - Kato, Yasufumi; Nishimura, Toshihide; , Jun Matsubayashi; Furukawa, Kinya; Nomura, Masaharu; Fujii, Kiyonaga; Nakamura, Haruhiko
No abstract available